When black women moves: Singularities of acting and thinking from slavery to the 21st century (TEL Tempo, Espaço e Linguagem, 2023)
From the struggle against enslavement to the organized Black feminist movement, Black women have produced forms of resistance and knowledge that disrupt the paradigms of the western white world. In many contexts, they are outsiders within, a position that gives them unique ways of conceiving the world. This papper presents a brief review of the epistemological and symbolic references of Black women's organizational models, their historical role in feminist movements and interviews with women who occupy prestigious professional positions to understand how the practical and theoretical teachings constructed by Black women impact to their professional choices and activities.